The correlation and agreement of montreal cognitive assessment, mini-mental state examination and abbreviated mental test in assessing the cognitive status of elderly people undergoing hemodialysis - Maryam Rahmani; Azar Darvishpour; Parand Pourghane (Wolters Kluwer Medknow Publications, 2022)
Background: Cognitive disorders are one of the most common disorders in elderly people with chronic renal failure. This study aimed to investigate the correlation and agreement of Montreal Cognitive Assessment (MoCA), Abbreviated Mental Test Score (AMTS), and Mini-Mental State Examination (MMSE) tests in assessing the cognitive status of elderly patients undergoing hemodialysis at Guilan University of Medical Sciences in north of Iran. Materials and Methods: This cross-sectional study was conducted on 84 elderly people undergoing hemodialysis. Inclusion criteria was having an age of 60 years old and older, hemodialysis treatment for at least 6 months, and having reading and writing skills. The Pearson correlation test, Intraclass Correlation Coefficient (ICC) test, and Bland-Altman plot were used for data analysis. Results: The majority of samples were in the age group of 60-65 years (28.57%) and the majority of them were male (66.66%). The results showed a significant positive correlation between MoCA and MMSE (r = 0.69, p = 0.001), between MMSE and AMTS (r = 0.64, p = 0.001), and between MoCA and AMTS tests (r = 0.62, p = 0.001). The results also showed a weak agreement between MoCA and MMSE tests (ICC = −0.11, p = 0.633), between MMSE and AMTS tests (ICC = −0.007, p = 0.369), and between MoCA and AMTS tests (ICC = −0.001, p = 0.780). Conclusions: Based on the results, these tools seem to complement each other. The inconsistency between cognitive tests indicates a serious need to develop appropriate instruments for detecting cognitive disorders in elderly.